Homogeneous Time-Resolved Fluorescence-Based Assay to Monitor Extracellular Signal-Regulated Kinase Signaling in a High-Throughput Format - Ayoub, Mohammed Akli; Trebaux, Julien; Vallaghe, Julie; Charrier-Savournin, Fabienne; Al-Hosaini, Khaled; Gonzalez Moya, Arturo; Pin, Jean-Philippe; Pfleger, Kevin D. G.; Trinquet, Eric (Frontiers in Endocrinology, 2014)
The extracellular signal-regulated kinases (ERKs) are key components of multiple important cell signalling pathways regulating diverse biological responses. This signalling is characterized by phosphorylation cascades leading to ERK1/2 activation and promoted by various cell surface receptors including G protein-coupled receptors (GPCRs) and receptor tyrosine kinases (RTKs). We report the development of a new cell-based phospho-ERK1/2 assay (designated Phospho-ERK), which is a sandwich proximity-based assay using the homogeneous time-resolved fluorescence technology. We have validated the assay on endogenously expressed ERK1/2 activated by the epidermal growth factor (EGFR) as a prototypical RTK, as well as various GPCRs belonging to different classes and coupling to different heterotrimeric G proteins. The assay was successfully miniaturized in 384-well plates using various cell lines endogenously, transiently or stably expressing the different receptors. The validation was performed for agonists, antagonists and inhibitors in dose-response as well as kinetic analysis, and the signalling and pharmacological properties of the different receptors were reproduced. Furthermore, the determination of a Z’-factor value of 0.7 indicates the potential of the Phospho-ERK assay for high-throughput screening of compounds that may modulate ERK1/2 signalling. Finally, our study is of great interest in the current context of investigating ERK1/2 signalling with respect to the emerging concepts of biased ligands, G protein-dependent/independent ERK1/2 activation, and functional transactivation between GPCRs and RTKs, illustrating the importance of considering the ERK1/2 pathway in cell signalling.